2015
DOI: 10.5271/sjweh.3537
|View full text |Cite
|
Sign up to set email alerts
|

Workplace bullying, sleep problems and leisure-time physical activity: a prospective cohort study

Abstract: Workplace bullying, sleep problems and leisure-time physical activity: a prospective cohort study by Hansen ÅM, Gullander M, Hogh A, Persson R, Kolstad HA, Willert MV, Bonde JP, Kaerlev L, Rugulies R, Grynderup MB No studies have so far evaluated the moderating role of leisure-time physical activity in relation to the association between workplace bullying and sleep problems. We found support for and increased risk of sleep problems among respondents reporting workplace bullying. High leisure-time physical act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…Bullying or mobbing is associated with early awakenings and lack of resting during sleep, as shown by longitudinal WBH and PRISME studies [ 58 ]. In fact, bullying and unwanted sexual attention is prospectively associated with long-term sickness absence, and this association is partially mediated by poor sleep [ 59 ].…”
Section: Part I Occupational Factors That Influence Sleepmentioning
confidence: 99%
“…Bullying or mobbing is associated with early awakenings and lack of resting during sleep, as shown by longitudinal WBH and PRISME studies [ 58 ]. In fact, bullying and unwanted sexual attention is prospectively associated with long-term sickness absence, and this association is partially mediated by poor sleep [ 59 ].…”
Section: Part I Occupational Factors That Influence Sleepmentioning
confidence: 99%
“…Psychological and psychosomatic reactions become more prominent and severe with persistent exposure. Illustrating these reactions, research shows that prolonged bullying is associated with subsequent reports of anxiety (8,15), depression (8,16), suicidal ideation (17,18), headache (19), and sleep problems (20)(21)(22). In a meta-analysis it was found that exposure to bullying predicted subsequent mental health complaints [odds ratio (OR) 1.68, 95% confidence interval (95% CI) 1.35-2.09] and somatic complaints (OR 1.77, 95% CI 1.41-2.22) after adjusting for baseline health status (9).…”
mentioning
confidence: 99%
“…The choice of distribution was determined by searching for the model that fitted the data best in terms of log-likelihood. The selection of possible confounding factors was based on previous publications and a priori reasoning[ 12 , 16 , 19 , 21 , 29 - 31 ]. In order to produce better confidence limits[ 28 ], we bootstrapped the CI estimates with 10000 replacements and a variance adjustment of 1.…”
Section: Methodsmentioning
confidence: 99%
“…Bullying may have considerable impact on the health and well-being for those being affected, including a higher risk of anxiety[ 7 - 9 ], depression[ 8 , 9 ], suicidal ideation[ 9 , 10 ], headache[ 9 , 11 ], and sleep problems[ 9 , 12 , 13 ]. In a meta-analysis it was found that exposure to bullying predicted subsequent increase in mental health complaints (OR = 1.68; 95%CI: 1.35-2.09) and somatic complaints (OR = 1.77; 95%CI: 1.41-2.22) after adjusting for baseline health status[ 14 ].…”
Section: Introductionmentioning
confidence: 99%